Pembangunan Aplikasi E-Learning Berbasis Android sebagai Media Pembelajaran di SMA Negeri 1 Bintan Menggunakan ADDIE Model - Zulfachmi, Zulfachmi; Zulkipli, Zulkipli; Rahmad, Abdul; Derry, Derry (Prosiding, 2024)
Education in the digital era has undergone significant transformation along with the development of information and communication technology that has presented various solutions to improve the effectiveness and efficiency of the learning process. The learning process at SMA Negeri 1 Bintan is still dominated by conventional methods that have limitations in flexibility. This study aims to develop an Android-based e-learning application as a solution to overcome these limitations. By using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model, this study identifies the needs of students and teachers, designs the interface and learning materials, develops the application, and implements it at SMA Negeri 1 Bintan. The evaluation was carried out through black box testing using all pair testing, equivalence partitioning, and use case testing techniques. The test results show that this e-learning application has good and stable performance in various usage scenarios. This application is suitable for use as a learning medium at SMA Negeri 1 Bintan, meets the needs of digital learning, and supports an effective learning process both online and offline.